Structural, spectral and potentiometric characterization, and antimicrobial activity studies of [Zn(phen) 2(cnge)(H 2O)](NO 3) 2·H 2O - López Tévez, Libertad Leonor (2012)
An octahedral Zn complex with o-phenanthroline (o-phen) and cyanoguanidine (cnge) has been synthesized and characterized. The crystal structural data show the formation of a ZnN5O core where the metal coordinates to two mutually perpendicular o-phenanthrolines as bidentate ligands [Zn–N bond lengths in the 2.124(2)–2.193(2) A˚ range], the cyanide nitrogen of a cnge [d(Zn–N) ¼ 2.092(2) A˚ , ff(Zn–N–C) ¼ 161.1(2)], and a water molecule [d(Zn– Ow) ¼ 2.112(2) A˚ ]. Spectral data (FT-IR, Raman, and fluorescence) and speciation studies are in agreement with the structure found in the solid state and the one proposed to exist in the solution. To evaluate the changes in the microbiological activity of Zn, antibacterial studies were carried out by observing the changes in minimum inhibitory concentration of the complex, the ligands, and the metal against five different bacterial strains. The antibacterial activity of Zn improved upon complexation in three of the tested strains.